Genistein Attenuates Acute Cerebral Ischemic Damage by Inhibiting the NLRP3 Inflammasome in Reproductively Senescent Mice - Wang, Shiquan; Wang, Jin; Wei, Haidong; Gu, Tingting; Wang, Jiajia; Wu, Zhixin; Yang, Qianzi (Frontiers in Aging Neuroscience, 2020)
Postmenopausal women have a higher incidence of stroke compared to the age-matched males, and the estrogen was thought to be the main cause of such difference. However, estrogen replacement therapy for the prevention of postmenopausal stroke shows controversial results and is widely disputed due to its serious side effects after chronic administration. Genistein (Gen), a natural phytoestrogen with fewer side effects, has a protective effect against cerebral ischemia damage. However, whether Gen could effectively prevent postmenopausal stroke has not been elucidated. In the current study, reproductively senescent mice were treated with Gen (10 mg/kg) for two weeks before having transient cerebral ischemia insults. Neurological scores, infarct volumes, and cell apoptosis were evaluated 24 h after reperfusion. The levels of inflammatory factors and nod-like receptor protein 3 (NLRP3) inflammsome-related proteins were also examined. The results showed that Gen treatment reduced infarct volumes, improved neurological scores, attenuated apoptosis, and decreased inflammatory factor release. The expression of NLRP3 inflammasome-related proteins in microglia was downregulated by Gen. However, the overexpression of NLRP3 in microglia abrogated the Gen-induced inhibition of inflammatory factor release and reversed the neuroprotective effect of Gen. Taken together, the results suggest that Gen treatment could attenuate the acute injury induced by cerebral ischemia in reproductively senescent mice via the inhibition of the NLRP3 inflammasome in microglia, indicating that Gen could be a candidate drug for the treatment of stroke in postmenopausal women.